Heavy Parliamentary v. Heavy Executive: Ambiguity of Power in Indonesian Constitutional Practices - Mukhlis, Muhammad Mutawalli; Wahab, Harlida Abdul; Paidi, Zulhilmi; Sastrawaty, Nila; Hasan, Haslinda (Fakultas Hukum, Universitas Muhammadiyah Yogyakarta, 2000)
The history of the Indonesian constitution has implemented Parliamentary and Presidential systems at different times. However, in practice it creates ambiguity in system implementation. The presidential system currently implemented is experiencing a dilemma due to regulation and separation of powers which tends to still have a parliamentary nuance. This research is library research that examines and explores regulatory documents, books, journals and other scientific works that are relevant to the topic of discussion. The results of data collection were analyzed in depth and then presented descriptively analytically. This article aims to provide ideas for building a concrete government system based on the shift in power functions that has occurred. This article concludes the need to issue a Law on the Presidential Institution which contains concrete limits on the powers of the President and the DPR. The President's capacity as head of government is limited by the party coalition in parliament. Therefore, it is necessary to redefine the roles and relationships between the President, DPR and political parties, clarify the checks and balances mechanism, and support the effectiveness of concrete and proportional government.